Clinical and diagnosis characteristics of breast cancers in women with a history of radiotherapy in the first 30 years of life: A French multicentre cohort study. Issue 2 (August 2017) - Demoor-Goldschmidt, C.; Supiot, S.; Oberlin, O.; Helfre, S.; Vigneron, C.; Brillaud-Meflah, V.; Bernier, V.; Laprie, A.; Ducassou, A.; Claude, L.; Mahé, M.A.; de Vathaire, F.
Abstract: Purpose: Irradiation (>3 Gy) to the breast or axillae before 30 years of age increases the risk of secondary breast cancer (SBC). The purpose of this article is to describe the clinical characteristics of SBC and the way of diagnosis in young women (before the age of national screening) in France who had received previous radiotherapy for a childhood or a young adulthood cancer. Patients and methods: This retrospective, multicentre study reviewed the medical records of women with SBC before the age of the national screening who had received irradiation (≥3 Gy) on part or all of the breast before 30 years of age, for any type of tumour except BC. Results: A total of 121 SBC were detected in 104 women with previous radiotherapy. Twenty percent of SBC were detected during regular breast screening and 16% of the women had a regular radiological follow-up. Conclusion: Our results points out that the main proportion of childhood cancer survivors did not benefit from the recommended breast cancer screening. This result is comparable to other previously published studies in other countries. A national screening programme is necessary and should take into account the patient's age, family history, personal medical history and previous radiotherapy to reduce the number of SBC diagnosed at an advanced stage.